2018
DOI: 10.1523/jneurosci.2501-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial Prefrontal Cortex Is Necessary for Normal Associative Inference and Memory Integration

Abstract: The ability to flexibly combine existing knowledge in response to novel circumstances is highly adaptive. However, the neural correlates of flexible associative inference are not well characterized. Laboratory tests of associative inference have measured memory for overlapping pairs of studied items (e.g., AB, BC) and for nonstudied pairs with common associates (i.e., AC). Findings from functional neuroimaging and neuropsychology suggest the ventromedial prefrontal cortex (vmPFC) may be necessary for associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 52 publications
9
71
0
Order By: Relevance
“…In this division of labor, the hippocampus is thought to encode details of unfolding events and reactivate details of past events, while the mPFC is thought to find commonalities across episodes and bias hippocampal reactivation towards relevant past events (Preston & Eichenbaum, 2013). In line with these predictions, patients with lesions to either the mPFC (Spalding et al, 2018) or the hippocampus (Pajkert et al, 2017) suffer deficits in the memory integration that cannot be explained by deficits in associative memory alone. As the nature of these lesions did not change between encoding and inference, however, these studies do not clarify whether these regions specifically impair integrative encoding.…”
Section: Episodic Memories Are Integrated Across Event Boundariesmentioning
confidence: 91%
“…In this division of labor, the hippocampus is thought to encode details of unfolding events and reactivate details of past events, while the mPFC is thought to find commonalities across episodes and bias hippocampal reactivation towards relevant past events (Preston & Eichenbaum, 2013). In line with these predictions, patients with lesions to either the mPFC (Spalding et al, 2018) or the hippocampus (Pajkert et al, 2017) suffer deficits in the memory integration that cannot be explained by deficits in associative memory alone. As the nature of these lesions did not change between encoding and inference, however, these studies do not clarify whether these regions specifically impair integrative encoding.…”
Section: Episodic Memories Are Integrated Across Event Boundariesmentioning
confidence: 91%
“…Although many behavioral and neuroimaging studies showed that reactivation of A during BC-learning can lead to interference and forgetting of C (Anderson, 2003;Kuhl et al, 2011), another outcome is episodic inference, where a relation is inferred between A and C. Although episodic inference can be achieved on-demand, from separate memories of individual events (Kumaran and McClelland, 2012), it can also result from memory integration, whereby new events are linked with prior related memories into a combined representation (Schlichting et al, 2014;Richter et al, 2016;Zeithamova and Preston, 2017). Notably, the same hippocampal-vmPFC interactions implicated in concept learning (Kumaran et al, 2009;Bowman and Zeithamova, 2018;Frank et al, 2019) have been implicated in memory integration and inference in both neuroimaging (Zeithamova et al, 2012; and lesion work (Dusek and Eichenbaum, 1997;Ryan et al, 2016;Spalding et al, 2018). Finally, the same regions have been shown to underlie schema-related memory (Tse et al, 2007(Tse et al, , 2011van Kesteren et al, 2012;Spalding et al, 2015;Brod et al, 2017;Gilboa and Marlatte, 2017;Gilboa and Moscovitch, 2017;Baldassano et al, 2018;Romero et al, 2019).…”
Section: Specific and Generalized Representations Supporting Categorimentioning
confidence: 99%
“…The source of the competitive interaction is unclear and could be due to increased demands such as task switching 4951 . Our finding that greater vmPFC deactivation was related to more interference suggest competition in some aspect of information integration functions supported by this region 5255 . Most studies employing a dual-task paradigm aimed to understand interference presented in performing tasks per se by measuring reaction time and found overlapped neural representation between two tasks, supporting interference due to competition for the same brain region 36,56 .…”
Section: Discussionmentioning
confidence: 58%